2018
DOI: 10.20944/preprints201809.0281.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Apoptotic Signaling in Axon Guidance

Abstract: Navigating growth cones are exposed to multiple signals simultaneously and have to integrate competing cues into a coherent navigational response. Integration of guidance cues is traditionally thought to occur at the level of cytoskeletal dynamics. Drosophila studies indicate that cells exhibit a low level of continuous caspase protease activation, and that axon guidance cues can activate or suppress caspase activity. We base a model for axon guidance on these observations. By analogy with other systems in whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Axon guidance cues have also been described to continue to function after target innervation. For example, repulsive axon guidance cues like semaphorin 3a (sema3a), Slit‐Robo and Eph‐Ephrins have been associated with cell death in multiple cell types after target innervation (Dickinson, Fegan, Ren, Hillier, & Duncan, 2011; Gagliardini & Fankhauser, 1999; Kellermeyer, Heydman, Mastick, & Kidd, 2018; H. Lee, Park, Kang, & Park, 2015; Wehner et al, 2016). Presumably, this is a way in which neurons innervating incorrect targets can be rapidly removed from a pool competing for neurotrophic factors derived from correct targets.…”
Section: Overview Of Progressive and Regressive Cues From Target Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Axon guidance cues have also been described to continue to function after target innervation. For example, repulsive axon guidance cues like semaphorin 3a (sema3a), Slit‐Robo and Eph‐Ephrins have been associated with cell death in multiple cell types after target innervation (Dickinson, Fegan, Ren, Hillier, & Duncan, 2011; Gagliardini & Fankhauser, 1999; Kellermeyer, Heydman, Mastick, & Kidd, 2018; H. Lee, Park, Kang, & Park, 2015; Wehner et al, 2016). Presumably, this is a way in which neurons innervating incorrect targets can be rapidly removed from a pool competing for neurotrophic factors derived from correct targets.…”
Section: Overview Of Progressive and Regressive Cues From Target Tissuesmentioning
confidence: 99%
“…Long‐distance regressive signaling has also been observed or suggested with axon guidance cue‐receptor pairs including semaphorin‐Neuropilin/Plexin, Slit‐Robo, Netrin‐deleted in colorectal carcinoma (DCC)/UNC‐5, and Eph‐Ephrin (Hamasaki et al, 2001; Kellermeyer et al, 2018; Marín et al, 2003; Wehner et al, 2016; Yue et al, 1999). Neurons are exposed to these repulsive cues at intermediate and final targets.…”
Section: Recent Evidence For Long‐distance Regressive Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is one of the processes of programmed cell death and is regulated by many genes and proteins . Studies have shown that apoptosis plays an important role in the process of IR injury .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Apoptosis is one of the processes of programmed cell death and is regulated by many genes and proteins. 14 Studies have shown that apoptosis plays an important role in the process of IR injury. 15 Apoptosis in the early reperfusion was found in clinical specimens and in animal models of flap IR injury 16,17 and apoptosis-related proteins play an important role in the process of apoptosis.…”
Section: Introductionmentioning
confidence: 99%